Scorpion cardiotoxicity: cardiotoxic effects of Parabuthus, the South African scorpion - Solomons, Hilary Denis (SA Heart Journal, 2019)
A range of cardiotoxic abnormalities occur in about one third to one half of patients with systemic envenomation. These effects include atrial tachycardia, ventricular extrasystoles, T wave inversions, ST-T wave changes and, less frequently, bundle branch block. Increased autonomic stimulation caused by increased vagal effects on the heart and sympathetic stimulation are the probable cause of these effects.